Updated procedures for calculating state-wide consumptive use in Idaho - Allen, Richard G., author; Robison, Clarence W., author; Wright, James L., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
Evapotranspiration and net irrigation water requirements were determined for 123 weather station locations across the state of Idaho for available periods of record. Estimates were made for daily, monthly and annual timesteps. Updated methods were employed for calculating reference evapotranspiration (ETr) and crop coefficients (Kc). The ET estimates cover a wide range of agricultural crops grown in Idaho and, in addition, ET estimates have been made for a number of native plant systems including wetlands, rangeland, and riparian trees. Estimates have been made for evaporation from three types of open water surfaces ranging from deep reservoirs to small farm ponds. The ET and net irrigation water requirement calculations are intended for use in design and management of irrigation systems, for water rights management and consumptive water rights transfers and for hydrologic studies. ET calculations have been made for all times during the calendar year including winter to provide design and operation information for managing land application of agriculture, food processing and other waste streams. The weather stations evaluated include 107 National Weather Service (NWS) cooperative stations measuring primarily air temperature and precipitation and 16 AgriMet agricultural weather stations. The AgriMet stations measure a full complement of weather data affecting evapotranspiration and are located primarily in the southern part of the state. Estimates at many stations cover more than 80 to 100 year periods of air temperature data. Because only maximum and minimum air temperature are observed at the NWS cooperative stations, the solar radiation, humidity and wind speed data parameters required in the ASCE Penman-Monteith equation (ASCE-PM) were estimated similar to recommendations in ASCE-EWRI (2005) where estimates for solar radiation (Rs) were based on differences between daily maximum and minimum air temperature and estimates for daily dewpoint temperature were based on daily minimum air temperature. Estimates for wind speed were based on long-term mean monthly summaries from AgriMet stations in southern Idaho and some airport locations in central and northern Idaho. Crop evapotranspiration, abbreviated ETc, was calculated on a daily timestep basis for improved accuracy. Daily calculation timesteps allowed for the calculation of evaporation of water from wet soil surfaces following precipitation or irrigation events. ETc for monthly, growing season and annual periods were summed from the daily calculations. Basal crop coefficient curves were developed or organized for 42 crop and land-cover types. Scheduling of irrigations was simulated to estimate soil evaporation from irrigation wetting events using a root-zone water balance.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.